Frequency of Endometriosis in females presenting with Infertility - Salma Khalid, Safoora Anjum, Arjumand Mahmood, Sadia Aman, Nadia Aman, Hira Tahir, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Infertility is an inability to get pregnancy or give birth to a child. Several factors may be involved in development of infertility. The endometriosis is the devastating syndrome which may be a cause of infertility in females. Aim: To assess the frequency of endometriosis in females presenting with infertility in a tertiary care hospital. Methods: This cross sectional study was conducted in the Department of Obstetrics & Gynecology, Services Hospital, Lahore for 6 months. 150 females underwent laparoscopic diagnosis of endometriosis. All this information was recorded on proforma. The collected data was entered and analysed statistically by using SPSS version 20. Results: The mean age of patients was 29.28±6.00years. The mean weight of females was 67.68±10.60kg, mean height was 1.60±0.05meters and mean BMI was 26.60±4.49kg/m2. The mean duration of marriage was 7.41±5.57years. In this study, 71 (47.33%) females had primary infertility while in 79 (52.67%) females had secondary infertility. There were 21 (14%) females who had endometriosis while 129 (86%) females did not have endometriosis. Conclusion: Thus the frequency of endometriosis was low in females with infertility but not ignorable.